(untitled) (Journal of Science and Technology, 2024)
Abstract Background In Africa, the elderly population is increasing at the fastest rate and this has become a burden as the rate is not proportional to the investment in health to meet their deteriorating health needs. Together with poor health care services, this creates discrepancies in access to health due to the financial limitations of the aged. Poor care services are related to poor knowledge, and bad perception hence this study seeks to explore the health practitioners’ level of knowledge, attitude, practice (KAP), and perception toward geriatric care. Methods Using a convenient sampling technique, 257 participants consisting of medical doctors, nurses, and physician assistants will be recruited within two months from three (3) polyclinic hospitals in the Ashanti Region (Tafo Government Hospital Suntreso Government Hospital and Kumasi South Hospital). A structured questionnaire will be used to assess KAP. Knowledge will be accessed by the use of the Knowledge about Older Patients Quiz (KOP-Q) while perception uses and attitude utilizes Nolan and Kogan’s attitude towards old people scale. Results The study will provide insight into the current state of geriatric care in the country especially among health practitioners. It will provide insight into the unique factors contributing to the quality of care health professionals give to the aged. Again, the study will offer the management of the respective hospitals the enormity of the problem (health professional’s knowledge, attitude, and practice of geriatric care) and put in measures to address them